Energy Conservation Through Energy Audit in U-TEC: A Case Study - Raut, Dhiraj; Poudel, Apshara; Mahato, Rachana Kumari; Pandey, Ramesh; Marahatha, Ashwin (Journal of UTEC Engineering Management, 2025)
An energy audit is a systematic process used to assess energy consumption patterns and identify opportunities for enhancing efficiency and reducing operational costs. This study focused on conducting a comprehensive energy audit at United Technical College (U-TEC), Chitwan, with an emphasis on lighting systems, ceiling fans, and solar integration. The total connected load was found to be 174.07 kW, with a maximum active power demand of 11.74 kW and a low load factor of 36.13%, indicating underutilization of installed capacity.The audit proposed replacing traditional lighting and fan systems with energy-efficient alternatives such as LED tube lights and BLDC fans, resulting in an estimated annual energy cost saving of Rs. 282,594.77 and a payback period of 2.38 years. Additionally, the integration of a 20-kW solar photovoltaic system was recommended, offering further savings and a projected payback period of 4.3 years. These findings demonstrate that strategic energy interventions can significantly reduce energy consumption, enhance sustainability, and lower operational costs for educational institutions.